Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3389/fphys.2016.00505
|View full text |Cite
|
Sign up to set email alerts
|

Short and Long Term Effects of High-Intensity Interval Training on Hormones, Metabolites, Antioxidant System, Glycogen Concentration, and Aerobic Performance Adaptations in Rats

Abstract: The purpose of the study was to investigate the effects of short and long term High-Intensity Interval Training (HIIT) on anaerobic and aerobic performance, creatinine, uric acid, urea, creatine kinase, lactate dehydrogenase, catalase, superoxide dismutase, testosterone, corticosterone, and glycogen concentration (liver, soleus, and gastrocnemius). The Wistar rats were separated in two groups: HIIT and sedentary/control (CT). The lactate minimum (LM) was used to evaluate the aerobic and anaerobic performance (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 44 publications
3
17
1
Order By: Relevance
“…The results obtained in the present work for the soleus musculature showed higher levels of SOD, and Catalase in group TD. Similar elevation of Catalase in the soleus muscle was found in a study using healthy animals exercised at 60% of maximum speed, with a single molecule of Catalase acting to convert millions of molecules of water and oxygen [43,44]. De ciency of Catalase has been shown to increase the effects of DM1 and increase the risk of type II diabetes in healthy individuals [45].…”
Section: Discussionsupporting
confidence: 53%
“…The results obtained in the present work for the soleus musculature showed higher levels of SOD, and Catalase in group TD. Similar elevation of Catalase in the soleus muscle was found in a study using healthy animals exercised at 60% of maximum speed, with a single molecule of Catalase acting to convert millions of molecules of water and oxygen [43,44]. De ciency of Catalase has been shown to increase the effects of DM1 and increase the risk of type II diabetes in healthy individuals [45].…”
Section: Discussionsupporting
confidence: 53%
“…Recently, it was shown that GC secretion might be provoked by different types of stressors [ 41 ]. Some of them link oxidative stress in skeletal muscles with hypermetabolism state and with stress response to situations such as burn trauma [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several investigations involving animal models of different backgrounds were published. Some examples include methodological analyses (de Araujo et al, 2007 ; Beck et al, 2012 ; Sena et al, 2015 ), effects of periodized or non-periodized training (de Oliveira et al, 2007 ; de Araujo et al, 2012 , 2013a , 2016 ; Scariot et al, 2016 ) effects of luminosity and time of day (Beck and Gobatto, 2013 , 2016 ; Beck et al, 2014 ; Beck et al, 2014a , b ) and comparion with the MLSS protocol (Rodrigues et al, 2016 ).…”
Section: Animal Models and The Lmtmentioning
confidence: 99%